DRIVING SCHOOL TRANSFORMATION THROUGH LEADERSHIP, INNOVATION, AND COLLABORATION: EVIDENCE FROM ST. PAUL SCHOOL, SUNTER JAKARTA - Yustina Sumarni (Sampoerna University, 2025)
This study explores how transformational leadership and educational innovation influence team success through stakeholder collaboration at St. Paul School, Sunter Jakarta. Using a quantitative research design with data from 110 respondents analyzed through PLS-SEM, the study reveals that transformational leadership does not directly enhance team success but exerts a significant indirect effect through stakeholder collaboration, indicating full mediation. Conversely, educational innovation demonstrates both direct and indirect positive effects on team success, suggesting partial mediation. These findings emphasize that leadership vision and innovation must be supported by strong collaborative engagement among teachers, parents, alumni, and the school foundation to achieve sustainable improvement. Theoretically, the results validate the integration of Transformational Leadership Theory, Innovation Diffusion Theory, and Stakeholder Theory, showing that collaborative synergy serves as the key mechanism driving school transformation and collective performance.